2016
DOI: 10.1016/j.eswa.2015.10.016
|View full text |Cite
|
Sign up to set email alerts
|

A review of computational methods applied for identification and quantification of atherosclerotic plaques in images

Abstract: Evaluation of the composition of atherosclerotic plaques in images is an important task to determine their pathophysiology. Visual analysis is still as the most basic and often approach to determine the morphology of the atherosclerotic plaques. In addition, computer-aided methods have also been developed for identification of features such as echogenicity, texture and surface in such plaques. In this article, a review of the most important methodologies that have been developed to identify the main components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 88 publications
0
34
0
Order By: Relevance
“…for the goals of materials informatics. For example, there has been a dramatic progress in automated analysis of medical images with different segmentation techniques 1012 .…”
Section: Introductionmentioning
confidence: 99%
“…for the goals of materials informatics. For example, there has been a dramatic progress in automated analysis of medical images with different segmentation techniques 1012 .…”
Section: Introductionmentioning
confidence: 99%
“…Conclusion has been drawn that each segmentation method with improvement, or in combination with other technique, could provide better performance [3, 4]. Clustering algorithms and supervised classification used for the segmentation of atherosclerotic plaques were analysed in [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the genesis and progression of atherosclerosis is directly correlated with the distribution of the hemodynamic forces and contributes to atherogenesis [4,9,22]. The mechanics of blood flow in the arteries of a person, the relationship between the geometry of the vessel and the progression of atherosclerotic plaques has been proven by various authors [3,8,14,17,19].…”
Section: Resultsmentioning
confidence: 99%